2010
DOI: 10.1186/1471-2164-11-s1-s6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of deep sequencing microRNA expression profile from human embryonic stem cells derived mesenchymal stem cells reveals possible role of let-7 microRNA family in downstream targeting of Hepatic Nuclear Factor 4 Alpha

Abstract: BackgroundRecent literature has revealed that genetic exchange of microRNA between cells can be essential for cell-cell communication, tissue-specificity and developmental processes. In stem cells, as in other cells, this can be accomplished through microvesicles or exosome mediated transfer. However, molecular profiles and functions of microRNAs within the cells and in their exosomes are poorly studied. Next generation sequencing technologies could provide a broad-spectrum of microRNAs and their expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 32 publications
2
104
0
2
Order By: Relevance
“…The proangiogenic activity of MVs derived from brain tumor cells was also reported [37], and MSC-MVs were found to protect the kidneys in a rat ischemia-reperfusion model [25]. Previous data have also demonstrated that MVs derived from other cell types, including platelets [32], endothelial progenitors [38][39][40][41], tumor cells [37,42], and ES-derived MSCs [43], have the proangiogenic activity both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 89%
“…The proangiogenic activity of MVs derived from brain tumor cells was also reported [37], and MSC-MVs were found to protect the kidneys in a rat ischemia-reperfusion model [25]. Previous data have also demonstrated that MVs derived from other cell types, including platelets [32], endothelial progenitors [38][39][40][41], tumor cells [37,42], and ES-derived MSCs [43], have the proangiogenic activity both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 89%
“…Since the observation that various types of RNAs are part of the cargo of extracellular vesicles (EVs) (Ratajczak et al 2006;Valadi et al 2007;Skog et al 2008), numerous efforts have been made to catalog RNA cargos and determine whether these RNAs are biologically functional (Luo et al 2009;Koh et al 2010;Nolte-'t Hoen et al 2012;Zhou et al 2012). The question of the functionality of the RNA cargos has been made complicated by the observation that a large proportion of the detected RNA biotypes are represented by a mixture of full-length and shorter fragments (Tuck and Tollervey 2011;Dhahbi et al 2013a,b;Vojtech et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…17 Dichas variantes incluyen RNA mensajeros y RNA reguladores tales como microRNA (miRNA) y RNA nocodificantes largos. 3,18,20 Los estudios de secuenciación de RNA de macrófagos (en reposo comparados con células activadas) demuestran que la inflamación altera importantemente el transcriptoma de dichas células. 21 De forma interesante, estudios del mismo tipo llevados a cabo comparando RNA exosomal derivado de macrófagos naïve y estimulados con lipopolisacárido (LPS) indican también alteraciones en el transcriptoma exosomal inducidas por la inflamación.…”
Section: Función Inmunorreguladora Del Rna Exosomalunclassified